2010
DOI: 10.1123/mcj.14.3.344
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Motor Learning in Patients with Parkinson’s and Alzheimer’s Disease: Differences in Learning Abilities?

Abstract: Experimental studies show intact implicit motor learning in patients with Alzheimer's disease (AD) but the results for patients with Parkinson's disease (PD) are inconclusive. This study tests implicit sequence learning in AD and PD patients, and healthy controls, using the classical Serial Reaction Time Task (SRTT), and a somewhat similar Pattern Learning Task (PLT), which involves stylus movements in different directions, and which allows detailed movement analysis. As expected, the time measures showed less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
1
23
0
2
Order By: Relevance
“…Additionally, we used higher-order probabilistic sequences, which again, was to model the types of associations with which people come into contact frequently. Our findings are similar to other studies examining sequence learning in people with PD that have shown impaired learning compared to controls (Wilkinson et al, 2009; van Tilborg and Hulstijn, 2010; Schendan et al, 2013), but in previous work, sequences were often deterministic (Ferraro et al, 1993), or participants were tested off of medication (Seidler et al, 2007), so the present study adds to the literature by testing a different type of learning in medicated participants. Nonetheless, our decision to test PD participants while they were medicated limits our ability to determine whether our results are due to medication or the disease itself.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, we used higher-order probabilistic sequences, which again, was to model the types of associations with which people come into contact frequently. Our findings are similar to other studies examining sequence learning in people with PD that have shown impaired learning compared to controls (Wilkinson et al, 2009; van Tilborg and Hulstijn, 2010; Schendan et al, 2013), but in previous work, sequences were often deterministic (Ferraro et al, 1993), or participants were tested off of medication (Seidler et al, 2007), so the present study adds to the literature by testing a different type of learning in medicated participants. Nonetheless, our decision to test PD participants while they were medicated limits our ability to determine whether our results are due to medication or the disease itself.…”
Section: Discussionsupporting
confidence: 92%
“…Sequence learning is typically assessed by removing the regularity at one or more points in training, to see whether response times are disrupted; the amount of disruption indicates the amount of sequence learning. Parkinson’s participants usually show impaired SRT learning compared to healthy older adults (Wilkinson et al, 2009; van Tilborg and Hulstijn, 2010; Schendan et al, 2013), but since the SRT has a large motor component, it is possible that motor deficits that occur in PD prevent this group from revealing learning. Additionally, because each event only occurs after a response to the previous event, participants’ responses control the timing between events, and these interstimulus intervals have been shown to affect the extent to which learning occurs and/or is expressed (Howard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Skillful communication, high levels of intensity and challenge, and integrating specifi c motor learning principles to exploit the strengths of IwAD may be key to a program's success. Motor learning tenets relevant to the AD population [35][36][37][38] include emphasizing implicit motor learning capacity, strategically using constant and blocked practice of skills, focusing on training of specifi c functional tasks, and recognizing the importance of repetition. Although IwAD may have diminished ability for explicit or declarative learning, implicit learning and memory appear to remain intact, [36][37][38][39] and through the use of this system, individuals maintain some ability for motor learning and relearning of skills.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that sequence learning was correlated to neuropsychological measures of executive functioning, namely spontaneous cognitive flexibility and the ability to shift attention. Consequently, limited executive functioning could weaken sequence learning and, as SRT tasks are used to test implicit learning, may explain the impairments in implicit motor learning found in PD (Siegert et al, 2006;van Tilborg & Hulstijn, 2010).…”
Section: The Impact Of Cognitionmentioning
confidence: 99%